Chapter Protecting Vagueira (Portugal) waterfront: preserving natural, recreational, residential, and commercial functions - Rita Pombo (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Vagueira is a Portuguese village hosting different economic and tourist-oriented activities, hence concerning a diversity of assets of interest. However, it has been affected by a persistent trend of erosion and experienced overtopping and flooding events in the past. The objective of this study was to determine the efficiency of deploying a detached breakwater in front of Vagueira beach in order to help protect the coastal community and safeguard its natural services and general assets.